Cesarean Section and Right Femur Fracture: A Rare but Possible Complication for Breech Presentation - Giampiero Capobianco; Giuseppe Virdis; Pietro Lisai; Claudio Cherchi; Ornella Biasetti; Francesco Dessole; Giovanni Battista Meloni (Case Reports in Obstetrics and Gynecology)
Background. The breech extraction of the fetus through the vagina has a greater risk of hip fracture compared with the extraction by abdominal route. Case. A 2390 g female infant was delivered at 39 weeks by elective cesarean section for breech presentation. The newborn sustained a fracture of the right femur. A simple immobilization of the limb in extension led to a complete healing of the fracture without sequelae. Conclusion. Caesarean delivery reduces the risk of causing a traumatic injury of the newborn compared to vaginal delivery, especially with breech presentation but does not eliminate this possible accidental complication.